Variation and succession of microbial communities under the conditions of persistent heavy metal and their survival mechanism. (January 2021) - Shuaib, Muhammad; Azam, Naila; Bahadur, Saraj; Romman, Muhammad; Yu, Qian; Xuexiu, Chang
Abstract: This review summarizes the recent papers published about the microbial communities under the conditions of persistent heavy metals around the world. Many microbial communities' study has demonstrated intense changes in the community composition, and microbial diversity caused by heavy metals, environmental pollution as well as adaptation processes allowing survival of microbes in metal-polluted ecosystems. The effect of heavy metals such as Cu, Pb, Hg, Ni, Cd, Zn, and As on soil microbial communities in mediated soil are reviewed. The different sensitivity measurement, toxicity of metals, relative toxicity is discussed. In recent years, industrial activities have a significant influence on the environment. Especially, heavy metals such as Hg, Cr, Pb, Mn, and As, have induced seriously affected the soil microbial communities, cause diseases and even death of organisms through contaminated soils, although heavy metals in trace amounts are beneficial even significant to organisms. The effect of heavy metals on soil microbial communities is still poorly understood. That how microbial communities respond to environmental changes is a key issue in ecology. In the future further work needed to understand the microbial community under persistent heavy metals, their effects, how to reduce and decrease the microbial diversity, and resistance of specific bacterial species to heavy metals. Highlights: To highlights the variation and succession of microbial communities. Study has demonstrated intense changes in the community composition, and microbial diversity caused by heavy metals. The environmental pollution as well as adaptation processes allowing survival of microbes in metal-polluted ecosystems. Microbial communities under the conditions of persistent heavy metal.